Crime Rates in the European Union Member States: A Legal and Comparative Analysis - Monika NIEDZWIECKA (Communications of International Proceedings, 2020)
The issue of crime is the subject matter of countless studies and research conducted across the world. Crime is a global problem plaguing mankind in every country and corner of the world. The only aspect that is different is the notoriety of crime and the characteristics of individual crimes. The aim of this paper is to compare crime rates in different EU member states. The paper offers a statistical analysis of crime that reveals the size, dynamics and structure of the most common criminal offences committed in the EU. The research is based on statistical data published by Eurostat, police and individual member states. Analysis of statistical data revealed a significant decline in the number of serious criminal offences, including homicide, assault and robbery that in the 2008-2017 period.
Keywords: Crime; Statistics; European Union.